The Collapse of the Family Institution and Adultery among Muslim Adolescents in Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2022)
The family institution is the key environment that shapes the lives of adolescents. Without proper monitoring and education from parents and family, adolescents are exposed to acts that can destroy their personality, such as engaging in adulterous activities. Therefore, this study was conducted to describe the family factors that contribute to adultery among Muslim adolescents in Malaysia. Adopting a qualitative method, 12 research participants were interviewed. The researcher used semi-structured interviews, which involve the flexibility of interviews with open-ended questions. The data obtained from the interview were then analyzed to obtain the results of the study. The findings of this study show that there are several family factors that have contributed to adultery. These factors are the divorce of parents, lack of communication between parents and children, excessive restrictions, lack of religious education, adulterous family, drug use and, the most serious of all, the family’s exploitation of adolescents for prostitution. These findings also indicate that the basis for the formation of  the Islamic family institution in Malaysia needs to be re-examined and monitored as well as possible in order to provide a safe environment for adolescents and, in turn, avoid adultery.Keywords: Personality, family factors, the collapse of the family institution, adolescents, Muslim, adulteryFull text: PDF